<h2>Steps</h2>
- Standard Form Equation: f(x) = ax² + bx + c
So firstly, since (0,5) is one of our values we can plug it into the standard form equation to solve for the c variable (since 0 will cancel out the a and b variable):
![5=a*0^2+b*0+c\\5=c](https://tex.z-dn.net/?f=5%3Da%2A0%5E2%2Bb%2A0%2Bc%5C%5C5%3Dc)
Now we know that the value of c is 5. Next, plug in (-1,12) into the standard form equation and simplify (remember to also plug in 5 for the c variable):
![12=a*(-1)^2+b*(-1)+5\\12=a-b+5\\7=a-b](https://tex.z-dn.net/?f=12%3Da%2A%28-1%29%5E2%2Bb%2A%28-1%29%2B5%5C%5C12%3Da-b%2B5%5C%5C7%3Da-b)
Next, plug (2,15) into the standard form equation and simplify:
![15=a*2^2+b*2+5\\15=4a+2b+5\\10=4a+2b\\5=2a+b](https://tex.z-dn.net/?f=15%3Da%2A2%5E2%2Bb%2A2%2B5%5C%5C15%3D4a%2B2b%2B5%5C%5C10%3D4a%2B2b%5C%5C5%3D2a%2Bb)
Now, with our last two simplified equations we will create a system of equations:
![7=a-b\\5=2a+b](https://tex.z-dn.net/?f=7%3Da-b%5C%5C5%3D2a%2Bb)
Now, I will be using the elimination method with this system. With the system, add up the equations together and you will get:
![12=3a](https://tex.z-dn.net/?f=12%3D3a)
From here, we can solve for the a variable. With it, just divide both sides by 3:
![4=a](https://tex.z-dn.net/?f=4%3Da)
Now that we know the value of a, plug it into either equation to solve for the b variable:
![7=4-b\\3=-b\\-3=b\\\\5=2(4)+b\\5=8+b\\-3=b](https://tex.z-dn.net/?f=7%3D4-b%5C%5C3%3D-b%5C%5C-3%3Db%5C%5C%5C%5C5%3D2%284%29%2Bb%5C%5C5%3D8%2Bb%5C%5C-3%3Db)
<h2>Answer</h2>
Putting all of our obtained values together, your final answer is:
![f(x)=4x^2-3x+5](https://tex.z-dn.net/?f=f%28x%29%3D4x%5E2-3x%2B5)